INFLUENCE OF COMPETITION IN THE PRIVATE SECURITY INDUSTRY ON THE MANAGEMENT OF PRIVATE SECURITY FIRMS IN NAIROBI CITY COUNTY, KENYA - Mavugano Lumadede, Alex Taban; Prof. Matthew M. Theuri, PhD,; Dr. Anthony Ngunyi, PhD, (Advances in Social Sciences Research Journal, 2021)
pThis study assessed the influence of external environmental factors on the management of private security firms in Nairobi County in Kenya. The specific objectives were to establish how competition in the private security industry influence the Management of Private Security Firms in Nairobi County Kenya. The study also sought to establish the moderating influence of Legal and Regulatory Framework on the management of Private Security Firms in Nairobi County. The study was guided by PESTEL Framework. This study used descriptive design with structured questionnaires as the instrument for data collection. The study conducted a multiple regression analysis to determine the relationship between competition in the private security industry and the management of private security firms. Results revealed that competition in the private security industry has a statistically significant and positive influence on the management of private security firms. The findings revealed that competition in the security industry has a positive and significant association with the Management of Private Security Firms in Nairobi County. Further, moderation findings revealed that Legal and Regulatory Framework moderates the relationship between the external environmental factors and management of Private Security Firms. The study concluded increased competition in the security industry such as due to entry of new players in the industry affect the strategy of the firms’ operations. The study recommends the management of Private Security Firms in Kenya adopt innovative strategies in order to remain competitive against entry of new players. The findings of this study may inform Government and other relevant security players such as KSIA, PSIA and PSRA in formulating policy frameworks for guiding their operations in the security industry./p